Involvement of CircRNA Expression Profile in Diabetic Retinopathy and Its Potential Diagnostic Value - He, Hengqian; Zhang, Juntao; Gong, Weikun; Liu, Mengyun; Liu, Hao; Li, Xiaoyong; Wu, Yufei; Lu, Qinkang (Frontiers in Genetics, 2022)
Background: Circular RNAs (circRNAs), a class of non-coding and indegradable RNAs, are research hotspots in recent years. The latest literature indicated that circRNAs possessed the advanced superiority for the early screening of diabetic retinopathy (DR). Methods: CircRNA sources of peripheral blood mononuclear cells (PBMCs) from healthy controls, diabetes mellitus (DM), and DR patients were extracted for circular RNA microarray analysis. Enriched biological modules and signaling pathways were analyzed by Gene Ontology enrichment and Kyoto Encyclopedia of Genes and Genomes analysis respectively. Real-time quantitative reverse transcription PCR (RT-qPCR) was performed to validate differentiated levels of several circRNAs (fold change≥3，p<0.05). Based on our clinical data from DR, the diagnostic performance of candidate circRNAs were measured by operating characteristic curves (ROC). Furthermore, their circRNA-miRNA networks were constructed with bioinformatics analysis. Results: Circular RNA microarray analysis was performed and 2452 and 289 circRNAs was screened with differential expression in DR patients compared to healthy controls or DM patients. Enrichment analyses showed that circRNAs in DR patients were enriched in extracellular matrix (ECM)-receptor interaction and focal adhesion pathways. The top 5 differential circRNAs in circRNA microarray analysis were subsequently verified by RT-qPCR. Consistently, a significant 2.2-fold reduction of hsa_circ_0095008 and 1.7-fold increase of hsa_circ_0001883 were identified in DR patients compared to DM. Compared with DM patients, the area under curve of hsa_circ_0095008 and hsa_circ_0001883 were 0.6710(95% CI, 0.5646 to 0.7775) (p = 0.003399) and 0.6071(95% CI, 0.4953 to 0.7189) (p = 0.06644) respectively, indicating a good diagnostic value. Conclusions: Our study provided a new inside for the treatment of DR and revealed the potential value of hsa_circ_0095008 and hsa_circ_0001883 as diagnostic biomarkers for early screening of DR patients.